PENGARUH MODAL KERJA, LIKUIDITAS, LEVERAGE DAN AKTIVITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN SEKTOR KESEHATAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2023 - Nurul Chairunnisa; Chairunnisa, Nurul; Munira, Mira; Andamari, Basis Gumilarsih (FEB-UP Press, 2025)
This research aims to provide empirical evidence regarding the effect of working capital, liquidity, Leverage and activity on profitability in health sector companies listed on the Indonesia Stock Exchange. Specifically, working capital is measured by Working Capital Turnover (WCTO), liquidity is measured by Current Ratio (CR), Leverage is measured by Debt to Equity Ratio (DER) and activity is measured by Total Asset Turnover (TATO). The sample selection was carried out using purposive sampling method, based on the criteria that have been determined, a sample of 12 health sector companies on the Indonesia Stock Exchange (IDX) during the 2019-2023 period was obtained. Based on the results of hypothesis testing, it shows that working capital has a significant effect on profitability, liquidity has a significant effect on profitability, Leverage has an effect on profitability, activity has an effect on profitability in health sector companies listed on the Indonesia Stock Exchange for the period 2019 to 2023.